China : Mid-Term Evaluation of China's Eleventh Five-Year - World Bank (World Bank, 2012)
This mid-term review has been undertaken to assess progress in the implementation of the Eleventh Five-Year Plan (11th 5YP) during its first two years and a half, draw preliminary lessons, and make recommendations for policy adjustments. The review examines the following strategic objectives: ensuring the stable operation of the macro economy and improving living standards; optimizing and upgrading of industrial structure; increasing energy efficiency; coordinating urban and rural development; improving basic public services; and enhancing sustainable development. Domestically, natural disasters-the severe storms, winter and the massive earthquake in Sichuan-took a heavy toll. Externally, global demand has slowed owing to the slump in the United States (U.S.) housing market and the related credit crisis and increased risk aversion. International oil, food, and other commodity prices have soared. These developments pose new challenges. But they also reinforce the appropriateness of the policy priorities of the 11th 5YP to increase the economy's resilience and ensure sustainable growth. The objectives and tasks set out in the 5YP are consistent with China's development challenges and government priorities Moreover, the quantitative indicators generally accord well with the overall guiding principles, orientations, and objectives, suggesting that these have been successfully put into operation.